Radiation Belt Losses: The Long‐Standing Debate Part II - L. W. Blum; F. Staples; A. Y. Drozdov; A. Michael; R. Millan; W. Tu; H. Zhao; A. Ukhorskiy; X. Fu (Earth and Space Science)
Abstract On 21 June 2022, during the annual Geospace Environment Modeling (GEM) workshop, a panel discussion titled “Radiation Belt Loss: The Long‐Standing Debate Part II” was organized by the focus group “System Understanding of Radiation Belt Particle Dynamics.” The panel focused on unresolved questions regarding the mechanisms driving electron loss in Earth's radiation belts, discussing topics including magnetopause shadowing, outward radial transport, and wave‐particle interactions driving particle precipitation. In this commentary, we provide an overview of the outcomes of this discussion and highlight future needs to better resolve outstanding questions.